Pachydermoperiostosis (Touraine-Solente-Gole Syndrome): A Case Report of Primary Hypertrophic Osteoarthropathy - Fatima Khurshid; Kinza Shahid Randhawa; Fatima Khurshid; Memoona Khalid (Journal of the Dow University of Health Sciences)
Pachydermoperiostosis (PDP), or primary hypertrophic osteoarthropathy (PHO), also known as the Touraine–Solente–Gole syndrome, is an autosomal dominant genetic disorder that is rare and is identified by finger clubbing, skin thickening, and periosteal growth. This case study details the case of a 21-year-old man with PDP to raise awareness, improve diagnosis, and enhance management strategies for the condition. The individual showed common signs like digital clubbing, pachydermia, and periostosis, as well as related symptoms like hyperhidrosis. Radiological imaging supported the diagnosis by revealing periosteal reactions and cortical thickening in multiple bones. Other conditions with comparable clinical characteristics were considered in the differential diagnosis, however, the diagnosis of PHO was confirmed by the specific radiological results and normal hormonal levels. The treatment primarily targets alleviating symptoms with drugs like Non steroidal antiinflamatory drugs (NSAIDs) and corticosteroids, along with newer options such as bisphosphonates. Timely detection and correct treatment are essential to enhance the well-being of people with PHO. This case study emphasizes the significance of tracking symptoms and offering thorough care to those with PDP/PHO.